Enterprise architecture as enabler of organizational agility : a municipality case study - Carvalho, Joana Amorim (2014)
Organizational agility is one of the top management concerns as organizations face today increasingly changing environments. Among enterprise architecture (EA) benefits, organizational agility has been claimed as one of them, perceived as a direct or indirect benefit, for example, through business-IT alignment, another top management concern. However, even with reasonable explanations in the EA literature, there is still a lack of empirical evidence to support such claim. Our research looks for that evidence seeking to understand how the development and use of EA may contribute for organizational agility. Having one of the biggest municipalities in the country as the research setting, using a mix-methods approach, a case study was carried out to identify EA artefacts, understand EA at use and examine agility in a specific change situation. In this case, enterprise architecture was not just used but was developed and improved during the change situation to enable organizational agility.